2021
DOI: 10.1186/s13020-021-00465-8
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptome analysis reveals the mechanism of acupuncture at PC6 improves cardiac function in myocardial ischemia model

Abstract: Background The pathological process of myocardial ischemia (MI) is very complicated. Acupuncture at PC6 has been proved to be effective against MI injury, but the mechanism remains unclear. This study investigated the mechanism that underlies the effect of acupuncture on MI through full-length transcriptome. Methods Adult male C57/BL6 mice were randomly divided into control, MI, and PC6 groups. Mice in MI and PC6 group generated MI model by ligatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Alternative splicing was one of the main mechanisms for protein diversity ( Yuan et al, 2021 ). We used rMATS to compare the difference in the inclusion level between the two groups of S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative splicing was one of the main mechanisms for protein diversity ( Yuan et al, 2021 ). We used rMATS to compare the difference in the inclusion level between the two groups of S .…”
Section: Resultsmentioning
confidence: 99%
“…Alternative splicing was one of the main mechanisms for protein diversity (Yuan et al, 2021). We used rMATS to compare the difference in the inclusion level between the two groups of S. rugosoannulata samples, evaluate the change of the corresponding inclusion level in the two samples, and obtain the distribution map of the differential alternative splicing events in each comparison group (Figures 5A-C).…”
Section: Characteristics Of Differential Alternative Splicing Events ...mentioning
confidence: 99%
“…Electroacupuncture (EA), a technique that involves stimulating acupuncture points with low-voltage electrical currents, has gained popularity as an alternative form of acupuncture [ 27 ]. Among the various acupuncture points, the PC6 on the Pericardium Meridian of Hand Jueyin is widely used for the treatment of cardiovascular conditions [ 28 , 29 ]. Furthermore, previous researches have demonstrated that EA can effectively reduce myocardial damage and limit the extent of MI [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%